Update on feline calicivirus: viral evolution, pathogenesis, epidemiology, prevention and control - Wei, Yanquan; Zeng, Qiaoying; Gou, Huitian; Bao, Shijun (Frontiers in Microbiology, 2024)
Feline calicivirus (FCV) is a prevalent and impactful viral pathogen affecting domestic cats. As an RNA virus, FCV exhibits high mutability and genetic plasticity, enabling its persistence within cat populations. Viral genetic diversity is associated with a broad spectrum of clinical manifestations, ranging from asymptomatic infections and mild oral and upper respiratory tract diseases to the potential development of virulent systemic, and even fatal conditions. This diversity poses distinctive challenges in diagnosis, treatment, and prevention of diseases caused by FCV. Over the past four decades, research has significantly deepened understanding of this pathogen, with an emphasis on molecular biology, evolutionary dynamics, vaccine development, and disease management strategies. This review discusses various facets of FCV, including its genomic structure, evolution, innate immunity, pathogenesis, epidemiology, and approaches to disease management. FCV remains a complex and evolving concern in feline health, requiring continuous research to enhance understanding of its genetic diversity, to improve vaccine efficacy, and to explore novel treatment options.